Prevalence of metabolic syndrome-like in the follow-up of very low birth weight preterm infants and associated factors - Luciana A. Heidemann; Renato S. Procianoy; Rita C. Silveira (Elsevier, 2019)
Objective: To assess the prevalence of metabolic syndrome-like symptoms in a population of preterm infants with very low birth weight (<1500 g) at 2 years of corrected age and identify the occurrence of associated risk factors. Methods: Cross-sectional study during a five-year period, including preterm infants born with very low birth weight evaluated at 2 years of corrected age. Metabolic syndrome-like symptoms was defined by the presence of three or more of these criteria: abdominal circumference ≥ 90th percentile, fasting blood glucose ≥ 100 mg/dL, triglycerides ≥ 110 mg/dL, HDL cholesterol ≤ 40 mg/dL, and blood pressure ≥ 90th percentile. Results: A total of 214 preterm infants with birth weight < 1500 g were evaluated. The prevalence of metabolic syndrome-like symptoms at 2 years of corrected age was 15.1%. Arterial hypertension was present in 57.5%, HDL ≤ 40 mg/dL in 29.2%, hypertriglyceridemia in 22.6%, and abdominal circumference above the 90th percentile in 18.8%. Only 3.7% had hyperglycemia. The presence of periventricular leukomalacia was an independent risk factor for arterial hypertension at this age (OR 2.34, 95% CI: 0.079-0.69, p = 0.008). Overweight and obesity at 2 years of corrected age were independently associated with metabolic syndrome-like symptoms (OR 2.75, 95% CI: 1.19-6.36, p = 0.018). Conclusion: Metabolic syndrome-like symptoms can be observed in very low birth weight preterm infants as early as 2 years of corrected age. Overweight and early-onset obesity are significant risk factors for metabolic syndrome-like symptoms, which deserves appropriate intervention for this high-risk population. Resumo: Objetivo: Avaliar a prevalência de síndrome metabólica "like" em população de crianças prematuras com muito baixo peso de nascimento (< 1500 gramas) aos dois anos de idade corrigida e identificar a ocorrência de fatores de risco associados. Métodos: Estudo transversal que incluiu prematuros nascidos durante um período de cinco anos com muito baixo peso de nascimento, avaliados aos dois anos de idade corrigida. A síndrome metabólica "like" foi definida pela presença de três ou mais desses critérios: circunferência abdominal ≥ percentil 90, glicemia de jejum ≥ 100 mg/dL, triglicerídeos ≥ 110 mg/dL, colesterol HDL ≤ 40 mg/dL e pressão arterial ≥ percentil 90. Resultados: Foram avaliados 214 prematuros abaixo de 1.500 gramas. A prevalência de síndrome metabólica "like" aos dois anos de idade corrigida foi 15,1%. Hipertensão arterial esteve presente em 57,5%, HDL ≤ 40 mg/dL em 29,2%, hipertrigliceridemia em 22,6% e aumento da circunferência abdominal acima do percentil 90 em 18,8%. Apenas 3,7% apresentaram hiperglicemia. A presença de leucomalácia periventricular foi um fator de risco independente para hipertensão arterial nessa idade (OR 2,34; IC 95% 0,079-0,69; p = 0,008); sobrepeso e obesidade aos dois anos de idade corrigida foram independentemente associados com síndrome metabólica "like" (OR 2,75, IC 95% CI 1,19-6,36; p = 0,018). Conclusão: Síndrome metabólica "like" ocorre em prematuros de muito baixo peso tão precocemente quanto dois anos de idade corrigida. Sobrepeso e obesidade de início precoce são fatores de risco significativos para síndrome metabólica "like", merecem intervenção apropriada para essa população de alto risco. Keywords: Preterm birth, Metabolic syndrome, Very low birth weight, Obesity, Arterial hypertension, Palavras-chave: Prematuridade, Síndrome metabólica, Muito baixo peso de nascimento, Obesidade, Hipertensão arterial